Long-Term Outcomes and Prognoses of Elderly Patients (≥65-Years-Old) With Distant Metastases From Well-Differentiated Thyroid Cancer During Radioiodine Therapy and Follow-Up - Qiu, Zhong-Ling; Shen, Chen-Tian; Sun, Zhen-Kui; Song, Hong-Jun; Xi, Chuang; Zhang, Guo-Qiang; Wang, Yang; Luo, Quan-Yong (Frontiers in Endocrinology, 2021)
Objective The objective of this study was to investigate the clinicopathological characteristics, long-term outcomes, and prognostic factors of elderly patients with distant metastases at initial diagnosis from well-differentiated thyroid cancer(WDTC) during radioactive iodine (131I) treatment and follow-up. Methods A retrospective review of medical records identified 183 elderly patients with DTC who underwent 131I treatment at our institution between 2006 and 2019. Results In total, 57 elderly WDTC patients with distant metastases were enrolled in this study. After 131I treatment, 32 (56.14%) patients had 131I avidity and 25 (43.86%) had non-131I avidity; 35 (61.40%) cases were classified as radioiodine refractory (RR)-WDTC and 22 (38.60%) as non-RR-WDTC. At the end of follow-up, 25 (43.86%) patients had died and 32 (56.14%) were alive. The 5- and 10-year overall survival (OS) rates were 71.50% and 30.49%, respectively, while the 5- and 10-year disease-specific survival (DSS) rates were 76.89% and 48.71%, respectively. Multivariate analyses showed that gross extrathyroidal extension and RR-DTC were independent prognostic factors for poor OS (P=0.04 and P=0.03, respectively), while gross extrathyroidal extension, extrapulmonary distant metastases, and RR-WDTC were independent prognostic factors for poor DSS at the end of follow-up (P=0.02, P=0.03, and P=0.02, respectively). Conclusions WDTC with distant metastases at initial diagnosis accounted for 31.15% of all elderly patients with DTC. Gross extrathyroidal extension and RR-DTC were the major factors associated with poor OS; gross extrathyroidal extension, extrapulmonary distant metastases, and RR-DTC were independent prognostic factors for poor DSS in elderly DTC patients with distant metastases.